Answer:
$420
Step-by-step explanation:
130x12=1560
165x12=1980
1980-1560=420
The different type of discount effected on the prices of two similar products having the same unit price may either increase or decrease the total unit price on the discounted sale price of the items.
Taking an hypothetical scenario :
50 ml of Product A = $100
60 ml of product A = $100
<u>Discount on sale of 60ml size on purchase of two or more units </u> : 10% off
Discounted price of 60 ml size :
Initial product cost on purchase of 3 units = ($100 × 3) = $300
Discounted price = (100 - 10)% × $300 = $270
<u>Discount on sale for 50ml size on purchase of two or more units</u> : $20 off
Discounted price of 50ml size :
This means $20 is deducted from any purchase of two or more units ;
Hence, purchasing 2 units of the 50 ml product will cost ; (
($100 × 2) - $20
$200 - $20 = $180
Therefore, the discount effected on the cost of product which has the same unit price may either decrease or increase the total cost of one product relative to the other.
Learn more :brainly.com/question/20418815
Answer:
49
Step-by-step explanation:
m^2-14m+c
Take the -14
Divide by 2
-14/2 = -7
Square it
(-7)^2 = 49
Add it to each side
m^2-14m+49
The value of c is 49
First, let us restate the given conditions
c is 5 more than variable a ( c = a + 5)
c is also three less than variable a (c = a - 3)
Now, lets look at the answer choices and or given
c = a − 5
c = a + 3
Here, c is 5 less than "a"...so automatically disqualified
a = c + 5
a = 3c − 3
Here, we have to get "C" by itself in both top and bottom equation.
So,
Simplified version :
c = a - 5
Here, c is 5 less than "a"...so automatically disqualified
a = c − 5
a = 3c + 3
Here also, we have to get "C" by itself in both top and bottom equation.
So,
simplified version:
c = a + 5
Here, c is 5 more than "a"...so we continue
c = (a - 3) / 3
Here, c is 3 less than "a" <u>divided by 3</u><u /> . So, this is not correct
c = a + 5
c = a − 3
Here, c is 5 more than "A"
Also, c is 3 less than "a"
Which satisfies the given.
So, our answer is going to be the last one:
c = a + 5
c = a - 3
Answer:
5
Step-by-step explanation: